The Context-Bound University Selectivity Premium - Joniada Milla (Institute of Labor Economics (IZA), 2017)
In this paper I present a selective survey of the empirical literature on wage premium to university selectivity focusing mainly on the context of the country under analysis and the identification strategies employed. I then estimate the wage premium to university selectivity using Canadian data and two popular methods to correct for non-random selection in universities of different quality: matching methods and instrumental variables (IV). I estimate a wage premium of 7% using the matching estimator, and a premium of 14.8% using the IV estimator for alumni of selective Canadian universities 4–6 years after graduation. My findings are in line with the literature on countries with a moderately differentiated higher education system that has low variation in tuition fees and is well supported by public funds.
Keywords: C21; I23; J30; 330; university selectivity; wage premium; context